A dynamic nomogram for predicting survival among diabetic patients on maintenance hemodialysis. Issue 1 (22nd July 2022) - Chen, Ying; Wang, Yao; Shen, Yan; Dai, Houyong; Huang, Xinzhong; Fang, Li; Huang, Xi; Shen, Yi; Yuan, Li
Abstract: Introduction: Among maintenance hemodialysis (MHD) patients, ones with diabetes mellitus (DM) are known to have the worst outcome. Methods: A total of 263 MHD patients were included, a dynamic nomogram was established based on multivariable Cox regression analysis. Results: The median overall survival (OS) time was 46 months. The 1‐, 3‐, and 5‐year OS rates were 90.9%, 70.5% and 53.9%, respectively. The multivariable Cox regression analysis indicated that DM duration, cardiovascular complication, baseline values before starting MHD for estimated glomerular filtration rate and serum phosphate were independent risk factors. The C‐index of the dynamic nomogram was 0.745 and the calibration curves showed optimal agreement between the model prediction and actual observation for predicting survival probabilities. Conclusions: Our study was the first to establish dynamic nomogram among diabetic MHD patients, the fast and convenient online tool can be used for individual risk estimation at the point of prognosis prediction.